A contiguous record of the SPICE event, sea‐level change and the first appearance of Fenghuangella laevis in Shandong Province, North China. (10th May 2021) - Ren, Guangying; Meng, Fanwei; Pulsipher, Mikaela A.; Schiffbauer, James D.; Yuan, Jinliang; Zhao, Yan; Guo, Ying; Gao, Jian; Chang, Chao
Abstract : Achieving accurate chronostratigraphical correlation between late Cambrian sections in North China and sections from elsewhere in the world has been a long‐standing problem, largely owing to a lack of preserved or identified biostratigraphical marker fauna. Here, we examine trilobite occurrences, the sequence of facies and lithological change, and carbon and oxygen isotopes from the carbonate sequence of the Jiulongshan section, Shandong Province. Whereas regionally comparable sections are commonly unconformable coincident with the Kushan–Chaumitien formation boundary, we report the Steptoean Positive Isotopic Carbon Excursion (SPICE) event from an uninterrupted section recording a regressive–transgressive palaeoenvironmental fluctuation. Further, we place the onset and rise of the SPICE event within a high‐resolution, trilobite biostratigraphical framework, reporting, for the first time, Fenghuangella laevis from Shandong Province. Although correlating trilobite biostratigraphical relationships from China to the rest of the world has long been burdened by the endemism of Chinese taxa, the base of the Fenghuangella biozone corresponds with the base of the globally recognized Glyptagnostus reticulatus biozone, thus better demarcating the base of the Paibian Stage in North China.